Acteurs locaux, representation et politics des eco-pouvoirs dans le Cameroun rural post-1994 - Oyono, P.R. (2006)
One of the major innovations in Cameroon’s forest industry is the devolution of management authority to local communities. These communities have viewed this shift as a response to their age-old demands — and frustrations — regarding profits from commercial harvesting of forests on their land base. The creation of community forests, local exploitation of those forests, and management of the income generated by sales of logs and timber, on the one hand, and access to forms of forest taxes by village communities, on the other hand, are significant factors in this change. The following lines briefly describe the basic mechanisms for this transfer of power over “nature and money.” They then explore the results generated by the “powers game” and local politics before assessing the role of local representatives — management committees — in the dynamics at work. Finally, working from the assumption that the observed limits arise to a large extent from the lack of benchmarks for decentralized management, the author proposes a research approach generally based on identifying indicators for monitoring the exercise of powers over the forest environment and forestry revenue.